The Effectiveness of North Macedonia’s Legal and Institutional Framework for Combating Human Trafficking - Gjorgi Slamkov (Review of European and Comparative Law)
Human trafficking is a global problem that fundamentally violates human freedoms and rights because a person is treated as an object exposed to various forms of exploitation, primarily sexual, forced labor, slavery, violation of bodily integrity, and other unlawful acts. The paper focuses on the normative and institutional framework of North Macedonia for combating human trafficking with an emphasis on effectiveness, i.e. the extent to which the established framework achieves its goal. The hypothesis of the research is that the creation of a national normative and institutional framework for combating human trafficking is not in itself a guarantee that it will be effective, i.e. that a substantive approach by the state is needed in the implementation of policies and the provision of the necessary resources for effectiveness. The research resulted in conclusions that point to several weaknesses in the framework for combating human trafficking in North Macedonia, including the lack of resources among competent institutions, inadequate sanctioning practices, weaknesses in coordination, and inadequate assistance and protection of victims. The paper contains several proposals for improving the effects of the fight against human trafficking, which are aimed at all segments of the social response through awareness-raising, education, prevention and repression. Several methods have been applied, namely, content analysis, historical and comparative methods. The paper also presents statistical data from several national and international institutions and organizations.